Portfolio as an alternative assessment effects on problem-solving performance, critical thinking, and attitude in mathematics - Belecina, Rene R. (2005)
The main purpose of this study was to find out the effects of alternative assessment on students' problem solving performance, critical thinking, and attitude in mathematics. The study employed a quasi experimental design specifically the pretest-posttest control-group design. Two intact groups of preservice mathematics teachers were used as participants. A problem-solving performance test, a critical thinking test, and an attitude scale were employed. It was revealed that students who were taught using the alternative assessment performed significantly higher in problem solving and critical thinking than those who were taught using traditional assessment. But there was no significant difference between their attitudes toward mathematics.
"October 2005."
Thesis (Ph.D. : Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematical ability -- Testing; Mathematics -- Study and teaching (Higher) -- Philippines -- Manila; Portfolios in education -- Philippines -- Manila